Sense of coherence and social support received by families of terminally ill cancer patients - Kurowska, Krystyna; Plechowska, Zofia (Contemporary Oncology/Współczesna Onkologia, 2008)
Cancer diagnosis affects not only the patient but also his or her family and caregivers. The aim of the study was to determine the relationship between the SOC (and its components) and level of social support received by the families of terminally ill cancer patients. The study included 62 relatives of patients of the ‘‘Światło’’ Hospice in Toruń. The SOC level was assessed using the Antonovsky SOC-29 questionnaire and social support was measured using the Kmiecik-Baran scale. The study shows that there is a relationship between comprehensibility and emotional support and between informative support and manageability. Examining these variables will help estimate the scope of care and adjust it to the caregivers’ needs, which might improve the quality of care provided by close relatives.